(untitled) (Móin-Móin Magazine - Studies in the Art of Puppetry, 2018)
This study analyses the experiences of the author as a theatre teacher and puppet theatre director at two important moments in her professional and artistic trajectory. Th e fi rst, when she founded and was director of the Puppeteer’s Studio in Bucharest, Romania, between the years of 1972 and 1976. The second moment relates to her activities as the creator and director of the École Nationale Supérieure des Arts de la Marionnette — ENSAM — [National Higher School for Puppet Arts], in Charleville-Mézières, France, 1987. Th e text highlights the distinct paths that are taken in the development of the actor-puppeteer. The article refl ects on teaching organized into principles of the transmission of inherited knowledge; teaching centred on experimentation and the personal choices of the student; and the tertiary 16 Revista de Estudos sobre Teatro de Formas Animadas MÓIN-MÓIN education institution. Rather than giving defi nitive and ready-made answers, the study aims to question, instigate and create questions about professional development in the complex fi eld of the art of puppet theatre. Keywords: Professional development, theatre schools, puppet theatre.